Population and development issues in Bangladesh : national plan of action based on ICPD'94 recommendations - Barkat, Abul.; Howlader, Sushil Ranjan (Dhaka : Ministry of Health and Family Welfare, Govt. of the People's Republic of Bangladesh, 1997)
Theme papers presented at a technical workshop held on December 17, 1996.
"Prepared on behalf of the National Committee for the Implementation of the Recommendations of the International Conference on Population and Development."
Includes bibliographical references.
Keywords: Bangladesh -- Population; Bangladesh -- Social policy